2005
DOI: 10.1243/095441105x9246
|View full text |Cite
|
Sign up to set email alerts
|

Compression-induced damage in a muscle cell model in vitro

Abstract: Soft tissue breakdown can be initiated at the muscle layer associated with bony prominences, leading to the development of pressure ulcers. Both the magnitude and duration of pressure are important factors in this breakdown process. The present study utilizes a physical model, incorporating C2C12 mouse myoblasts in a homogeneous agarose gel, to examine the damaging effects of prolonged applied pressure. Identical cylindrical cores cut from the agarose/cell suspension were subjected to two separate compressive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
1
13
1
Order By: Relevance
“…13,18,20,29 A previous cell-model study examining relative values of apoptotic and necrotic cell death revealed an increase in the apoptotic percentage of total cell death from 61% to 67% (10% increase) and 71% (16% increase) after 8 and 12 h of 10% compression, respectively. 35 In the present study, the apoptotic contribution was comparable, as summarized in Table 3. Thus after 22 h the percentages had increased to approximately 25% for uncompressed samples (both normoxic and hypoxic), whereas compressed samples incorporated 40-45% of apoptotic cell death.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…13,18,20,29 A previous cell-model study examining relative values of apoptotic and necrotic cell death revealed an increase in the apoptotic percentage of total cell death from 61% to 67% (10% increase) and 71% (16% increase) after 8 and 12 h of 10% compression, respectively. 35 In the present study, the apoptotic contribution was comparable, as summarized in Table 3. Thus after 22 h the percentages had increased to approximately 25% for uncompressed samples (both normoxic and hypoxic), whereas compressed samples incorporated 40-45% of apoptotic cell death.…”
Section: Discussionsupporting
confidence: 69%
“…A few studies have utilized in vitro model systems with a controlled experimental input. 8,35 In the present study, such an in vitro model was applied to study the relative contributions of hypoxia and compression to the progression of cell death in engineered skeletal muscle tissue. Hypoxia was considered to be the most important effect of ischemia in development of tissue damage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Single cell studies 54,56,75 showed that under excessive compressive strains, cell membranes initially form blebs followed by complete failure and rupture. In vivo testing in rats 6 showed that after prolonged loading, loss of muscle fiber cross-striation is encountered as well as infiltration of inflammatory cells as necrosis ensues.…”
Section: Dti Alters the Magnitude And Distribution Of Strain In Loadementioning
confidence: 99%
“…The model system has demonstrated that a prolonged compression period will increase the proportion of damaged muscle cells [84]. It is tempting to extrapolate this cell deformation data to the clinical setting, where tissue breakdown, in the form of pressure ulcers, may be induced within relatively short periods of continuous loading.…”
Section: Musclementioning
confidence: 99%